Factors associated with the career choices of high school seniors in the Cagayan Valley College of Arts and Trades - Tan, Alice Palattao 1926- (1976)
The main purpose of the study was to identify the factors which were associated with the career choices of 283 high school seniors of CVCAT enrolled in the academic year 1975-1976. It determined whether their career choices were associated with some variables, namely: sex, sibling rank, parents' educational attainment, family income and trade courses taken in high school. It also attempted to find out the reasons behind the seniors' career choices, the person/s influential in their career choices, and the implications of the findings for the improvement of the curriculum in CVCAT.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Cagayan Valley College of Arts and Trade -- Students; Vocational guidance -- Cagayan Valley